STUDI PENGARUH PERLAKUAN AGING TERHADAP KETAHANAN KOROSI PADUAN MGâ6Y - Permata Putri, Devi
Magnesium and its alloys have some potential as biomaterial implant. It is because magnesium has better biocompatibility with human physiology and has mechanical properties which similar to human bone. Compared to other biomaterial metals such as titanium alloys, stainless steel, and cobalt–chromium based alloys; magnesium alloys show elastic modulus similar to human bone that can prevent stress shielding effect on human bone. Besides that, magnesium is the fourth most abundant element in human body and very important for metabolism in various biological mechanism. Mg2+ ions resulting from degradation process can help the healing and growth of tissue. One of magnesium alloys that can be applicated as bone implant is Mg–6Y. But in reality, it has poor corrosion resistance. In this research, the effect of aging on corrosion resistance of Mg–6Y was studied. Aging was carried out at a temperature of 500oC for 1 h, 4 h, 24 h, 72 h, and 120 h after solution treatment at 250oC for 2 h. Then, corrosion testing was carried out by using immersion test in ringer lactate solution for 72 h. In addition, hardness test and metallography were also carried out. Results of this research show that corrosion rate of Mg–6Y tend to decrease after aging was given to the specimen. Hardness value and grain size increase as the aging time increase.